The DaimlerChrysler merger – a cultural mismatch? - Hollmann, Julia; Carpes, Aletéia de Moura; Beuron, Thiago Antonio (Revista de Administração da UFSM, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> American company Chrysler Corporation due to differences in the organizational cultures involved or due to a so-called ‘clash of culture'. What happens when two successful car producers with different know-how and a different knowledge background, different work processes, different product portfolios and last but not least, completely different corporate cultures decide to merge? Daimler-Benz and Chrysler wanted to strengthen their position during economically difficult times for the car industry by juggling the crisis together and they hoped to be able to combine their strengths. Therefore the two companies decided to fuse in 1998. But not even ten years later Daimler-Benz once again sold all its shares of the Chrysler division. The dream to become the third biggest car producer of the world, behind General Motors and Ford, burst. The expected and wished for synergy effects stayed out. Instead of gaining competitive advantage over their competitors, the merger rushed the two car producers ever deeper into the crisis and did not provide the companies with the necessary tools to overcome the recession. The presented paper deals with the failed merger of the German company Daimler-Benz with the U.S. American company Chrysler Corporation due to differences in the organizational cultures involved or due to a so-called ‘clash of culture'.